Neuromuscular fatigability of trunk extensors and flexors following 10 weeks of specifik exercise at devices - Alexander, N.; Ullrich, B.; Stening, J.; Felder, H.; Hökelmann, A. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
A deficiency in lower back muscle endurance is a risk-factor for low-back pain (Demoulin et al, 2006). This study analyzed the effects of 10 weeks of endurance-oriented strength training for the major trunk muscles on maximum voluntary isometric capacity (MVC) of the major trunk muscle groups and EMG estimated neuromuscular fatigability of the trunk extensors and flexors. Methods: Adolescent regional athletes were separated into two groups: training group (n = 11) and control group (n = 10). The total duration of the experimental period was 13 weeks. The first two weeks were used as a control period. Thereafter, training subjects started a 10 weeks progressive strength training period for the trunk extensors, flexors, lateralflexors and rotators on training machines equipped with a biofeedback system. Testing was performed during the baseline (weeks -2, -1) and after 10 weeks of training. Measurements included MVC force measurements of the major trunk muscles and analysis of the neuromuscular fatigue resistance of specific trunk muscle groups. Surface EMG of m. erector spinae, m. latissimus dorsi, m. rectus abdominis and m. obliquus externus was collected during sustained isometric trunk extension and flexion contractions at 40% of pre-exercise MVC. Results: No significant enhancement for any parameter was detected in controls. Significant increases in MVC of the major trunk muscle groups and endurance time during sustained isometric trunk extensions and flexions occurred following training. Normalized [% Max pre fatigue] EMG-RMS values of all analyzed muscle groups were higher during the fatiguing contractions at the first baseline compared to the second baseline measurement and the end-measurement. However, no significant differences in normalized EMG-RMS values during fatiguing trunk extensions occurred among the second baseline testing and the end-measurement. Contrary, significant lower normalized EMG-RMS values of the analyzed trunk flexor muscles were found after the training period compared to both baseline measurements. Discussion: The present exercise increased the maximum voluntary isometric capacity and endurance-time during sustained isometric trunk extensions and flexions in adolescent athletes. EMG-RMS analysis during fatigue suggests a rapid learning effect, rather than training-induced alterations. Although without statistical significance, average EMG activity during fatigue was lower after training indicating some neuromuscular adaptations. The present results indicate that baseline variability in EMG traces has to be considered when neuromuscular fatigability is analyzed in training studies.